Homeschooling in Chile. Report National Survey Results - Lester Aliaga Castillo (Pontificia Universidad Católica del Perú, 2017)
In 2014 a survey to gather information about families who practice homeschooling in Chile took place. They answered 67 families on the reasons that took the values they care, forms of socialization, the sources to develop the curriculum and time management for learning. This work is part of a larger research on home education in Chile.